(untitled) (Journal of Engineering, 2024)
The effect of the addition of sustainable materials and alkali-resistant glass fibers on perlite concrete is studied in this paper. The research includes slump, density, flexural strength, split tensile strength, compressive strength, and thermal conductivity tests. This specimen was cast using Portland cement, metakaolin (which replaced 15% of the cement weight as pozzolanic materials), a combination of coarse and fine perlite aggregate, superplasticizer, and local ash (which was employed as a filler and replaced by cement weight in a ratio of 10%). The ratio of cement to perlite (volumetric ratio) was 1:2. The concrete reinforced 1% alkali resistance glass fibers by volume of concrete. The results show that adding sustainable materials to the concrete increased its cylinder compressive strength by a percentage of (57.75%, 41.76%, and 44.82%) for 7,28 and 60 days, respectively and both tensile and flexural strength increased at a ratio of (37.28%, 30.33% and 34.5%), (36.05%, 68.22% and 56.52%) respectively at (7,28 and 60 days). And including alkali-resistant glass fibers increases the compressive, tensile and flexural strength in a ratio of (61.5%, 43.58%, 47.45%), (61.54%, 44.08% and 52.71%) and (113.95%, 124.3% and 97.85%) respectively at (7,28 and 60 days), compared with reference mix. The density increased by adding sustainable materials and fibers but stayed within the limitations of structural lightweight concrete (ASTM C330). The thermal conductivity also increased after adding sustainable materials and glass fibers compared with the reference mix, but it was within the constraints of insulation concrete.